2016
DOI: 10.1016/j.ygeno.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes of heterogeneous cell populations in the Ishikawa cell line during long-term culture: Proposal for an in vitro clonal evolution model of tumor cells

Abstract: Genomic changes in tumor cell lines can occur during culture, leading to differences between cell lines carrying the same name. In this study, genome profiles between low and high passages were investigated in the Ishikawa 3-H-12 cell line (JCRB1505). Cells contained between 43 and 46 chromosomes and the modal number changed from 46 to 45 during culture. Cytogenetic analysis revealed that a translocation t(9;14), observed in all metaphases, is a robust marker for this cell line. Single-nucleotide polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 26 publications
4
45
0
Order By: Relevance
“…Recent reports based on high‐resolution copy number profiling have demonstrated that clones dominating in early cultures of cancer cell lines frequently disappear, to be replaced by related, but distinct clones with partly different genotypes . This is sometimes accompanied by an increased growth rate and a loss of clonal heterogeneity, indicating that a selection of more over less proliferative clones takes place under the nutrient rich conditions of culture (examples are depicted in Figure A‐C).…”
Section: Cell Lines Change Genetically Over Timementioning
confidence: 97%
See 2 more Smart Citations
“…Recent reports based on high‐resolution copy number profiling have demonstrated that clones dominating in early cultures of cancer cell lines frequently disappear, to be replaced by related, but distinct clones with partly different genotypes . This is sometimes accompanied by an increased growth rate and a loss of clonal heterogeneity, indicating that a selection of more over less proliferative clones takes place under the nutrient rich conditions of culture (examples are depicted in Figure A‐C).…”
Section: Cell Lines Change Genetically Over Timementioning
confidence: 97%
“…These alterations occur even under standardized, unchanged culture conditions. Notably, most studies penetrating the issue in depth have shown that the altered genetic profiles result not as much from an accumulation of mutations in vitro as from changes in the clonal composition of cultured cells …”
Section: Cell Lines Change Genetically Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…However, the differences are not significant to characterize each cell line because genetic components between cell lines carrying the same name can be changed during cell culture (Kasai et al 2016). This can be found in the human STR database, showing that all STR loci are not always identical between the same cell lines registered at different cell banks.…”
Section: Resultsmentioning
confidence: 99%
“…The worst-case scenario is that bottlenecking selection procedures for the effects of newly purchased FBS batches on the different cell types are visible or measurable only in the rarest cases. Elimination of ancestral clones by sequential selection, possibly by unsuitable FBS charges on sophisticated cell culture, could result in replacement by novel clones that are genetically still identical but equipped with modified features (Kasai et al, 2016). A recent comparison of experimental methods for reproducible pharmacogenomic profiling of cancer cell line panels highlighted evidence that even the amount of FBS in growth media could have an impact (Haverty et al, 2016).…”
Section: Human Platelet Lysates (Hpl) 411 Hpl In Animal and Human Cmentioning
confidence: 99%